1986
DOI: 10.1177/030089168607200304
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Factors in Italian Women: A Multicentric Case-Control Study

Abstract: To evaluate the importance of several risk factors for breast cancer in the Italian female population, a large multicentric case-control study was conducted in 10 breast clinics in Italy. The study included 1,556 women affected by breast cancer, histologically and/or cytologically confirmed. Controls were 1,505 women admitted to a hospital in the same town, matched with cases for residence and with the same age distribution of the Italian female population. The risk factors considered in this study were family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…No significant associations were revealed between body mass index and breast cancer for pre-and postmenopausal women. This is of particular interest since several case-controls studies have demonstrated positive associations between BMI and breast cancer among postmenopausal women (2,4,7,8,15,17,18,(20)(21)(22)25,29) and inverse associations among premenopausal women (7,17,20). However, the reports from previous findings have not included African-Americans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant associations were revealed between body mass index and breast cancer for pre-and postmenopausal women. This is of particular interest since several case-controls studies have demonstrated positive associations between BMI and breast cancer among postmenopausal women (2,4,7,8,15,17,18,(20)(21)(22)25,29) and inverse associations among premenopausal women (7,17,20). However, the reports from previous findings have not included African-Americans.…”
Section: Discussionmentioning
confidence: 99%
“…The findings to date suggest that an interaction exists between BMI and menopausal status in relationship to breast cancer. Case-control studies have demonstrated relatively consistent positive findings between BMI and increased breast cancer risk for postmenopausal women (2,4,7,8,15,17,18,(20)(21)(22)25,29).…”
Section: Introductionmentioning
confidence: 96%
“…In particular, the risk of developing the disease increases with higher calculated body mass index (BMI = body weight (kg) 7 height (m 2 )) [1][2][3][4][5][6][7]. Weight gain per se and body fat have also been implicated to play a role in breast cancer development [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, only 14 of 2 reliability studies4, 5 showed an important difference in reporting errors between cases and controls. Furthermore, the distribution of estimates of effect abstracted from such case‐control studies6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 does not differ substantially from the distribution of estimates of effect abstracted from studies that assessed termination status by prospective self‐report or by retrospective record‐based report in which the record of termination status predated diagnosis33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45 (Fig. 1).…”
mentioning
confidence: 99%